Answer:4x2−6x−4
Step-by-step explanation:
(4x+2)(x−2)
=(4x+2)(x+−2)
=(4x)(x)+(4x)(−2)+(2)(x)+(2)(−2)
=4x2−8x+2x−4
=4x2−6x−4
Answer:
you really did not give us the full pictuer
Step-by-step explanation:
First we look for the area of the triangle which is given by:
A = (1/2) * (4) * (6)
A = 12 feet ^ 2
Area of the rectangles:
Rectangle 1:
R1 = (4) * (8)
R1 = 32 feet ^ 2
Rectangle 2:
R2 = (6) * (8)
R2 = 48 feet ^ 2
Rectangle 3:
R3 = (root (6 ^ 2 + 4 ^ 2)) * (8))
R3 = 57,68882041 feet ^ 2
The total area will be:
A = 2A + R1 + R2 + R3
Substituting values:
A = 2 * (12) + 32 + 48 + 57,68882041
A = 161.6888204 feet ^ 2
Answer:
The total area of the prism is:
A = 161.6888204 feet ^ 2
Answer:
34'2" I think
Step-by-step explanation:
You just add them together and that was for the first part
There no solution sorry man